Análisis Comparativo de Residuos de Construcción Generados en un mismo Modelo de Vivienda con Sistema Tradicional vs. Diseño Modular - Quirós-Martínez, Claudio (Instituto Tecnológico de Costa Rica, 2012)
In many projects, specially in dwellings construction, the traditional system involves to build with Patarrá blocks and concrete columns; this situation has produce a lot of waste which are not quantified. In response, the modular system of Modublock has been imposed for to reduce waste and optimize materials. This document pretends to make a quantified waste comparative analysis in the same dwelling model, one of the traditional system, and the other with modular system of Modublock. The economical and environmental impact was also determinated. Field measurements were made in Verolís residential project, located in Heredia. Wastes quantified were: steel, concrete, bricklaying mortar, coat mortar and concrete blocks. Even it was evaluated the utilization and durability of reusable plywood phenolic formwork. The concrete is the material that produces more wastes. Modular blocks are wasted by 0,15%, caused by mistakes on transportation, and near 0,90% of Patarrá blocks, caused by mistakes on transportation and settings. The traditional system involves more time at activities, therefore higher manpower costs about modular system. For evaluate environmental impact, it was developed an ecological footprint matrix in both systems, in order to determinate the required earth surface to produce construction materials, and the necesary area for waste.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2012.
Keywords: Modublock; LEAN; Formaleta fenólica; Huella ecológica; Coordinación modular